Molecular Identification of Wedgefishes Stingrays (Rynchobatus sp.) at PPI Rigaih, Aceh Jaya Regency by using COI Gene - Amin, Waldi; Bahri, Samsul; Malik, Danie Al; Yusmalinda, Ni Luh Astria; Ningsih, Enex Yuniarti; Pertiwi, Ni Putu Dian; Sembiring, Andrianus (Universitas Teuku Umar, 2023)
Indonesia is one of the largest shark and ray producing countries in the world. Based on FAO (Food and Agriculture Organization) data, Indonesia is the top country which produce plenty of sharks and rays every year. One of the stingray shark caught by the fishermen called ikan pari kekeh (kekeh stingray), data from the IUCN( International Union for Conservation of Nature and Natural Resources) this ray is included in Red List and categorized in Appendix II CITES (Convention on international trade of endangered species) due to excessive fishing. In most cases, the identification of kekeh ray is not easy because the information and conservation data are very limited. This study was conducted to identify the species of kekeh stingray landed at Rigaih Fish Landing Port, Aceh Jaya Regency using the COI gene (Cytochrome c oxidase subunit I) molecular analysis. Sampling was carried out in June 2021 and then analysed at Indonesian Biodiversity Foundation (BIONESIA) laboratory. The analysis results were adjusted to GenBank data via BLAST (Basic Local Alignment Search Tools). The results of the analysis found per value. The ident of 10 samples ranged around 99-100% each and the query qover value each sample is 100%. The farthest genetic distance value is 0.34. The phylogenetic tree managed to classify species from each sample and form a cluster together with the data obtained from the NCBI genbank